Beam instability in the vicinity of beam extraction region of negative ion source. Issue 1 (1st April 2022) - Nagaoka, K.; Nakamoto, R.; Sasaki, T.; Hamajima, T.; Nakano, H.; Ikeda, K.; Fujiwara, Y.; Osakabe, M.; Takeiri, Y.; Tsumori, K.
Abstract: Beam instability in the presheath region of negative ion beam extraction is investigated in theoretically and experimentally. The linear stability analysis shows that the beam instability is unstable due to coupling between positive ion flow and negative ion flow. On the other hand, no clear activity can be seen in the experiment in the frequency range predicted by the theory. The beam instability in the presheath region of negative ion beam extraction may not cause the degradation of the beam focusing because of collisional damping and/or Landau damping.